DAKWAH MANAGEMENT OF COMMUNITY DEVELOPMENT - Lubis, Zulkarnain (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2020)
Community Development Management is an effort to integrate new ideas and ideas by organizing, planning and utilizing existing resources to change society to a better state. Da'wah in Islam is an effort to invite people to the right path that is pleasing to Allah SWT. Today's da'wah is not enough to be interpreted as an activity of amar ma'ruf nahi mungkar, but furthermore da'wah can be interpreted as an effort to create the benefit of human life according to their respective fields. Da'wah and community development cannot be separated, because the target of da'wah in Islam is humans without exception. Humans, sociologically and culturally always experience changes, this is where da'wah acts as an agent of change in society that always leads people to a better direction. Society in life is always changing and the change is not always for the better, even vice versa. Humans will experience a crisis of identity as a noble creature in the sight of Allah, therefore da'wah also undergoes changes in accordance with the social transformation that develops along with the progress of science and technology. In the current era of technology, Islamic society should show its existence in the eyes of the world. The development of Islamic society is demanded in all fields and still holds fast to the ideals and struggles of the Prophet in the da'wah of Islam. To prove the development of the Islamic community is not only by way of da'wah bil-lisan but more shown by da'wah bil-hal.